THE INFLUENCE OF ISOLATED FABULATING FROM SMOKING OF TOBACCO ON THE INDICATORS OF FUNCTIONAL ADAPTATION FOR MILITARY SERVICEMENTS WITH PRECEDING UNDERGROUND WORK IN THE COAL MINE - Дмитрий Владимирович Чуркин; Дмитрий Олегович Ластков; Валерий Шабанович Мамедов (Medicina v Kuzbasse, 2017)
Indicators of functional adaptation of servicemen who have previous experience of underground work in coal mines.